Graphene and its Derivatives-Based Optical Sensors - Gao, Xiao-Guang; Cheng, Ling-Xiao; Jiang, Wen-Shuai; Li, Xiao-Kuan; Xing, Fei (Frontiers in Chemistry, 2021)
Being the first successfully prepared two-dimensional material, graphene has attracted extensive attention from researchers due to its novel properties and wide range of applications. In particular, graphene and its derivatives have displayed several ideal properties, including high surface-to-volume ratio, ability to quench fluorescence, excellent biocompatibility, broadband light absorption, and strong polarization-dependent effects, thus emerging as one of the most popular platforms for optical sensors. Graphene and its derivatives-based optical sensors have numerous advantages, such as high sensitivity, low-cost, fast response time, and small dimensions. In this review, recent developments in graphene and its derivatives-based optical sensors are summarized, covering aspects related to fluorescence, graphene-based substrates for surface-enhanced Raman scattering (SERS), optical fiber biological sensors, and other kinds of graphene-based optical sensors. Various sensing applications, such as single-cell detection, cancer diagnosis, protein, and DNA sensing, are introduced and discussed systematically. Finally, a summary and roadmap of current and future trends are presented in order to provide a guideline for the future development of graphene and its derivatives-based optical sensors.